Chemical Versus Enzymatic Nucleic Acid Modifications and Genomic Stability - Jonathan R. Cortez; Marie E. Migaud (DNA)
DNA damage and repair have been central themes in cellular biology research. Broadly, DNA damage is understood as modifications to canonical nucleotides that disrupt their function during transcription and replication. A deeper biochemical understanding of DNA damage is essential, as the genome governs all cellular processes. We can classify DNA damage according to whether the modifications to the nucleic acid scaffold are chemically or enzymatically initiated. This distinction is important because chemical modifications are often irreversible, sometimes sparse, and difficult to detect or control spatially and replicate systematically. This can result in genomic damage or modifications to nucleotides in the nucleotide pool, which is less commonly studied. In contrast, enzymatic modifications are typically induced by the cell for specific purposes and are under strong regulatory control. Enzymatic DNA modifications also present a degree of sequence specificity and are often reversible. However, both types of DNA modifications contribute to cellular aging when poorly repaired and, as a result, remain incompletely understood. This review hopes to gather less studied mechanisms in nucleotide modifications and show research gaps in our current understanding of nucleotide biology. By examining the implications of these mechanisms on DNA modifications, in the nucleotide pool and genome, we may gain insights into innovative strategies for mitigating the effects of cellular aging.